2009
DOI: 10.1007/s00264-008-0715-8
|View full text |Cite
|
Sign up to set email alerts
|

Recombined bone xenografts enhance tendon graft osteointegration of anterior cruciate ligament reconstruction

Abstract: The objective of the study was to discover whether recombined bone xenograft (RBX), a porous solid material, could augment healing of the tendon-to-bone interface after anterior cruciate ligament (ACL) reconstruction. ACL reconstruction was performed bilaterally in 25 skeletally mature rabbits using long digital extensor tendon grafts. RBX was implanted into the treated knee, with the contralateral knee serving as control. Three rabbits were killed at postoperative weeks two, six and 12 for routine histology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…However, the slow degradation rate of injectable CPC could block the ingrowth of new bone and might delay the osteointegration process (19). therefore, recombined bone xenograft (RBX), a new type of biosynthetic material which can be directly incorporated into injectable CPC, has been suggested to be more effective in augmenting bone ingrowth in animal models (20). RBX has already been used as a BMP carrier, showing accelerated tendon-bone healing (21).…”
Section: Bone Proteins and Growth Factorsmentioning
confidence: 99%
“…However, the slow degradation rate of injectable CPC could block the ingrowth of new bone and might delay the osteointegration process (19). therefore, recombined bone xenograft (RBX), a new type of biosynthetic material which can be directly incorporated into injectable CPC, has been suggested to be more effective in augmenting bone ingrowth in animal models (20). RBX has already been used as a BMP carrier, showing accelerated tendon-bone healing (21).…”
Section: Bone Proteins and Growth Factorsmentioning
confidence: 99%
“…16,84,85,89,101 The beneficial effects of the granulocyte colony stimulating factor (GCSF) is related to the production of granulocytes and stem cells in bone marrow, differentiation of neutrophils, angiogenesis, and differentiation and migration of mesenchymal stem cells. 27,70,74,88,90,92,98,104 BMPs are signaling proteins that influence tissue structures in the body, and they have a role in skeletal development. 92 Application of growth factors such as basic fibroblast growth factor (bFGF) and vasculoendothelial growth factor and stem cells merits further investigation but is not immediately clinically applicable.…”
Section: Strategies To Enhance Tendon Graft-bone Tunnel Healingmentioning
confidence: 99%
“…It recently has been shown that administration of bFGF resulted in enhanced mesenchymal cell proliferation, collagen preservation, enhanced neovascularization and circulation, improved tissue maturation, which resulted in increased structural and mechanical properties of the injured tendons. 74 The demineralized bone matrix (DBM) is a further source of BMPs, which has been proposed as a mean of enhancing tendon-bone healing and tendon-bone fixation strength by inducing an increase in the growth of fibrocartilage and mineralized fibrocartilage at the tendon bone interface in ovine. 27,70,74,88,90,92,98,104 BMPs are signaling proteins that influence tissue structures in the body, and they have a role in skeletal development.…”
Section: Strategies To Enhance Tendon Graft-bone Tunnel Healingmentioning
confidence: 99%
“…Bone samples can be used as a source of natural BMPs. Pan et al studied the effect of applying recombined bone xenograft within the bone tunnels after ACL replacement [ 43 ]. The xenograft was used to produce BMPs, which were then mixed with cancellous bone and formed into cylinders which were attached to the ends of tendon grafts and implanted in the tibial and femoral bone tunnels in rabbit models.…”
Section: Alternative Augmentation Materialsmentioning
confidence: 99%